2006
DOI: 10.1021/jp0556557
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of Reaction of OH with 1,3-Butadiene

Abstract: The kinetics of the reaction of hydroxyl radical with 1,3-butadiene at 240-340 K and a total pressure of approximately 1 Torr has been studied using relative rate combined with the discharge flow and mass spectrometer technique. The reaction dynamics of the same reaction has also been investigated using ab initio molecular orbital theory. The rate constant for this reaction was found to be negatively dependent on temperature, with an Arrhenius expression of k1 = (1.58 +/- 0.07) x 10(-11) exp[(436 +/- 13)/T] cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 26 publications
9
55
0
4
Order By: Relevance
“…The observed negative activation energy (E a /R ) -664 K) is in reasonable agreement with the value of E a /R ) -440 K obtained by Li et al 20 and the value of E a /R ) -470 K obtained by Atkinson et al 27 The negative temperature dependence observed for the OH + 1,3-butadiene reaction is consistent with a reaction mechanism that is dominated by OH addition to the double bond through the formation of a long-range complex 39 rather than by H-abstraction even at the low pressures and high temperatures of these experiments. Although the negative temperature dependence and absence of a pressure dependence could indicate a hydrogen-abstraction mechanism through a pre-reactive complex, similar to that observed in the OH + acetic acid reaction, 40 previous measurements of the products of the OH + 1,3-butadiene reaction and theoretical calculations of the potential energy surface suggest that H-abstraction is a minor product channel.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The observed negative activation energy (E a /R ) -664 K) is in reasonable agreement with the value of E a /R ) -440 K obtained by Li et al 20 and the value of E a /R ) -470 K obtained by Atkinson et al 27 The negative temperature dependence observed for the OH + 1,3-butadiene reaction is consistent with a reaction mechanism that is dominated by OH addition to the double bond through the formation of a long-range complex 39 rather than by H-abstraction even at the low pressures and high temperatures of these experiments. Although the negative temperature dependence and absence of a pressure dependence could indicate a hydrogen-abstraction mechanism through a pre-reactive complex, similar to that observed in the OH + acetic acid reaction, 40 previous measurements of the products of the OH + 1,3-butadiene reaction and theoretical calculations of the potential energy surface suggest that H-abstraction is a minor product channel.…”
Section: Resultssupporting
confidence: 92%
“…[17][18][19][20] The reaction of 1,3-butadiene with the hydroxyl radical is considered to be the dominant chemical loss process during the daytime, with lifetimes of 1 and 4.5 h for OH concentrations of approximately 2 × 10 6 and 8 × 10 5 molecule cm -3 . 20,21 A generic mechanism for the OHinitiated oxidation of 1,3-butadiene is shown below: Under atmospheric conditions, the butadiene-OH adducts react with O 2 to form peroxy radicals that subsequently react in the presence of NO to form alkoxy radicals and NO 2 . 17,22,23 The major identifiable products observed from the OH-radicalinitiated oxidation of 1,3-butadiene in the presence of NO are acrolein, 19,[23][24][25][26] furan, 19,22,23,26 formaldehyde, 17,25,26 4-hydroxy-2-butenal, 26 and organic nitrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 reveals that the attack of OH Å on the double bond of the substrate does not actually require a barrier. This is understandable since experimental and computational data for OH attack on double bonds reveal reactions that are virtually diffusion controlled [53][54][55]. Since I O-O requires a small barrier to generate a meso-hydroxylated product (1.7 kcal/mol), P meso , the OH Å attack on the C@C bond of 1 will compete favorably with this degradation process.…”
Section: Epoxidation Of 1 By Cpd 0 Via An O D Attackmentioning
confidence: 99%
“…It is a product of industrial processes [28,29], tobacco smoke [30], and motor vehicle exhaust [31]. It can react in the atmosphere with OH [32], Cl [33] and O 3 [34][35][36] forming a series of products. In 1999, Kramp et al [36] performed experimental studies on the reaction of ozone with 1,3-butadiene at room temperature and atmosphere pressure.…”
Section: Introductionmentioning
confidence: 99%